EQUALITY AND NON DISCRIMINATION PRINCIPLES IN PROVIDING RIGHTS WITH DISABILITIES - Rantau Itasari, Endah (Jurnal Komunikasi Hukum (JKH), 2020)
With the increasingly escalating discrimination against groups of people with disabilities, humanity will then be made aware of the importance of recognizing that they are the same human beings as others, equal in rights and free in making choices. Therefore there are special rights for groups of people with disabilities. Special rights are not privileges, but they are granted so that persons with disabilities are able to maintain their unique identity, characteristics and traditions. Special rights such as non-discriminatory treatment are equally important to achieve the same treatment. Therefore the principle of equality, and non-discrimination (non-discrimination) becomes very important in human rights.